Entanglement of photonic modes from a continuously driven two-level system - Jiaying Yang; Ingrid Strandberg; Alejandro Vivas-Viaña; Akshay Gaikwad; Claudia Castillo-Moreno; Anton Frisk Kockum; Muhammad Asad Ullah; Carlos Sánchez Muñoz; Axel Martin Eriksson; Simone Gasparinetti (npj Quantum Information)
Abstract The ability to generate entangled states of light is a key primitive for quantum communication and distributed quantum computation. Continuously driven sources, including those based on spontaneous parametric downconversion, are usually probabilistic, whereas deterministic sources require accurate timing of the control fields. Here, we experimentally generate entangled photonic modes by continuously exciting a quantum emitter - a superconducting qubit - with a coherent drive, taking advantage of mode matching in the time and frequency domain. Using joint quantum state tomography and logarithmic negativity, we show that entanglement is generated between modes extracted from the two sidebands of the resonance fluorescence spectrum. Because the entangled photonic modes are perfectly orthogonal, they can be transferred into distinct quantum memories. Our approach can be utilized to distribute entanglement at a high rate in various physical platforms, with applications in waveguide quantum electrodynamics, distributed quantum computing, and quantum networks.